Open‐label study of etanercept treatment in patients with moderate‐to‐severe plaque psoriasis who lost a satisfactory response to adalimumab. (19th July 2017) - Bagel, J.; Tyring, S.; Rice, K.C.; Collier, D.H.; Kricorian, G.; Chung, J.; Iles, J.; Stolshek, B.S.; Kaliyaperumal, A.; Papp, K.A.
Summary: Background: Some patients with plaque psoriasis experience secondary failure of tumour necrosis factor inhibitor therapy. Objectives: To evaluate efficacy, safety and patient‐reported outcomes (PROs) with etanercept in patients with secondary adalimumab failure. Methods: This phase IV open‐label single‐arm estimation study (NCT01543204) enrolled patients on adalimumab who had achieved static Physician's Global Assessment (sPGA) score 0/1 (clear/almost clear). Patients subsequently lost response, defined as sPGA ≥ 3 or loss of 50% improvement in Psoriasis Area and Severity Index (PASI 50). At baseline, patients had involved body surface area ≥ 10%, sPGA ≥ 3 and PASI ≥ 10. Antiadalimumab antibodies (ADAs) were measured at screening. Patients received etanercept 50 mg twice weekly for 12 weeks, followed by 50 mg weekly. The primary end point was sPGA 0/1 at week 12 (intention‐to‐treat analysis; no hypothesis tested). Additional outcomes included rates of sPGA 0/1, PASI responses, safety, PROs of itch, pain and flaking, Dermatology Life Quality Index, treatment satisfaction and Work Productivity and Activity Impairment questionnaire. Results: Sixty‐four patients enrolled; 67% had ADAs. sPGA 0/1 rates at week 12 were 39·7% [95% confidence interval (CI) 27·6–52·8; primary end point] and 45% (95% CI 29·3–61·5) for patients positive for ADAs and 35% (95% CI 15·4–59·2) for patients negative for ADAs. PASI 75 response rates at week 12 were 47·5% (95% CI 31·5–63·9) for patients who were positive for ADAs and 50% (95% CI 27·2–72·8) for patients negative for ADAs. No new safety signals were observed. PROs of itch, pain and flaking consistently improved at week 12 and were maintained through week 24. Conclusions: Patients with psoriasis who experienced secondary failure of adalimumab achieved satisfactory response to etanercept regardless of ADA status. Abstract : What's already known about this topic? Some patients with plaque psoriasis who achieve an adequate response with a tumour necrosis factor (TNF) inhibitor therapy, such as adalimumab, eventually lose their response. What does this study add? Patients who had lost their response to adalimumab subsequently achieved a clinical response to the TNF inhibitor etanercept, and no new safety signals were observed. Response to etanercept was not affected by the presence of antiadalimumab antibodies. Linked Comment: Albrecht and Gerdes. Br J Dermatol 2017;177 :338–339